2008
DOI: 10.1186/1471-2458-8-292
|View full text |Cite
|
Sign up to set email alerts
|

Health related quality of life measured by SF-36: a population-based study in Shanghai, China

Abstract: Background: Health related quality of life (HRQL) is a research topic that has attracted increasing interests around the world over the past two decades. The 36-item Short Form (SF-36) is a commonly used instrument for measuring HRQL. However, the information on Chinese adults' quality of life is limited. This paper reports on the feasibility of using the Mandarin version of SF-36 to evaluate HRQL in the population of Shanghai, China.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

19
128
3
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 144 publications
(151 citation statements)
references
References 19 publications
19
128
3
1
Order By: Relevance
“…[2][3][4] Disease labels and treatment lead to changes in lifestyle that may also affect healthrelated quality of life (HRQoL) and influence the adherence to treatment, a major issue nowadays for the treatment of hypertension and other chronic diseases. 5 Studies have mostly shown worst quality of life of patients with hypertension, [5][6][7][8][9][10] but other studies contradict these findings. 11,12 A systematic review of 20 original contributions identified lower quality of life among hypertensive individuals in most but not all studies.…”
Section: Introductionmentioning
confidence: 58%
See 1 more Smart Citation
“…[2][3][4] Disease labels and treatment lead to changes in lifestyle that may also affect healthrelated quality of life (HRQoL) and influence the adherence to treatment, a major issue nowadays for the treatment of hypertension and other chronic diseases. 5 Studies have mostly shown worst quality of life of patients with hypertension, [5][6][7][8][9][10] but other studies contradict these findings. 11,12 A systematic review of 20 original contributions identified lower quality of life among hypertensive individuals in most but not all studies.…”
Section: Introductionmentioning
confidence: 58%
“…Quality of life in all domains and summary component scores of SF-12 were also lower in hypertensive compared with normotensive individuals; these findings are similar to those reported in other population-based surveys and in studies performed in outpatient clinics and hospitals. [6][7][8][9][10][11][12]23 High diastolic BP (X110 mm Hg) and the presence of target-organ damage were also associated with lower scores of HRQoL in the domains of bodily pain, vitality and general health among patients with hypertension. 24 There is less association of hypertension with low quality of life than there is with other conditions, such as arthritis, diabetes, depression, congestive heart failure, lung disease and coronary heart disease.…”
Section: Discussionmentioning
confidence: 99%
“…The SF-36 dimension scores were compared with available data from nurses in New Zealand and general population in China (Shanghai province) ( Table 3) 1,27) . The nurses in this study had higher score in VT dimensions than that of nurses in New Zealand, while had lower score in GH dimensions, and others were similar to nurses in New Zealand.…”
Section: Resultsmentioning
confidence: 99%
“…Health related quality of life (HRQOL) is an individual's satisfaction or happiness with the dimensions of life insofar as they affect or are affected by health 1) . It contains a multidimensional concept embedded in physical, mental, cultural and social context.…”
Section: Introductionmentioning
confidence: 99%
“…Life quality according same scale was critical (Emotional Role Functioning, General Health, Bodily Pain). The graph shows the survey results of female from Iran (age -65-69 years) [17], China (age >60 years) [14], Japan (age 65 years) [1], Brazil (age -60-69 years) [11], USA (age -78 years) [13], Canada (age -65-74 years) [10], South Australia (age -65-74 years) [6], Poland (age -45-65 years) [19], Ukraine (own data).…”
Section: Resultsmentioning
confidence: 99%